Гражданское пространство Украины: степень идентификации и факторы консолидации - Злобина, Е.; Резник, А. (Социология: теория, методы, маркетинг, 2006)
The article deals with the problem of civil selfidentification from the standpoint of identifying oneself as a social actor within a spatioterritorial community. The authors pioneer the study of “intersection” of civil identity and its other kinds as well as investigate the distinguishing features of coexistence and interaction between different civil identities. In the paper, spatioterritorial selfidentification during 1992–2006 is examined, socialdemographic factors of spatioterritorial selfidenti fication are researched, and indicator of identification level among population in the Ukrainian civil space is defined.